The haunting of pip parker - Fine, Anne (Walker London, 1992)
Lots of children find it difficult to sleep on Christmas Eve, because they are excited, but Pip Parker is scared. Every night she's been lying awake watching the skull shape gleaming from her wall. Why is it haunting her?